Triathlon hub a proposed multisport training complex - Brito, Mary Joyce O.
Triathlon, a multisport event that requires its participants to swim, bike, and run in continuum is currently one of the rapidly growing sports worldwide. Countryside as the most common venue for trainings and competitions, triathlon clearly advances sports tourism in different parts of the world. Thus, corresponding to the undergraduate thesis theme for this academic year, entitled "Architecture is more fun in the Philippines : architecture and tourism", the researcher had chosen multisport as the main topic of her thesis. consequently, the main problem of this thesis is to design a facility that shall utilize multisport, mainly focusing on triathlon, to promote tourism and healthy lifestyle among its guests. Aside from reading books and magazines about triathlon, conducting interviews and surveys among triathlete were the methods used to gather the essentials for endurance training. The researcher also went on a triathlon event to immerse with the tri community, and to eventually get familiarized with their activities and the preparations hours before the race. Fortunately, other countries have established their triathlon centers already and these similar facilities, both the yet intangible and existing, were used as references in determining spaces neede. The vision of this project is to spearhead future multisport training facilities in the country. It also envisions being the first one-stop shop for multisport in the hilippines that shall generate tourism opportunities through providing complete facilities from sports instruction, endurance training, conditioning, lodging and recorvery.